PENGARUH MACAM MULSA DAN DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Ambarsari, Widi Komala; Maryani, Yekti; Susilaningsih, Sri Endah Prasetyowati (JURNAL ILMIAH AGROUST, 2019)
This study aims to determine the effect of mulch type and cow manure dosage on the growth and yield of cultivated peanut plants. Experiments were carried out at the "Lestari Makmur" self-help agriculture and pedestrian training center in April-June 2018, in the Polaman hamlet, Argorejo village, Sedayu sub-district, Bantul district, Yogyakarta, altitude of about 88 meters above sea level, and temperature between 26ºC-32ºC. Regosol soil type. The experiment was conducted using a factorial 3x3 trial with 1 control, which was arranged in a completely randomized block design (RAKL). The treatment consists of 2 factors. The first factor is the type of mulch consisting of 3 levels, namely: straw mulch, husk mulch, plastic mulch and one control. Both doses of cow manure consisting of 3 levels: 10, 15 and 20 tons haˉ¹. Each treatment was repeated 3 times. Observations included plant height, number of leaves, stover fresh weight, dry weight, weight of 100 seeds, number of filled pods / plants, weight of fresh pods / plants, dry pod weight / plants, fresh pod weight / plot, dry pod weight / plot and seed weight / hectare. The results showed that the treatment of mulch did not affect growth. The treatment of cow manure dosage had no effect on growth. The treatment of plastic mulch and husk mulch gave higher yields than straw mulch and control. The treatment of 10 kg / m² cow manure treated the results The highest treatment of cow manure doses gives the highest yield than control